Caracterização genética de populações ex situ de Leontopithecus chrysomelas (Kuhl, 1820) (Primata, Callithricidae) - Orefice, Gisele (2015)
Captive programs of breeding and management of threatened species act as a safeguard against a likely extinction of species in the nature. The model species in this study, Leontopithecus chrysomelas or golden headed lion tamarin (MLCD), has populations maintained in captivity in order to ensure a representative genetic diversity, since its natural habitat has been undergoing gradual loss and fragmentation. In contrast to which occurs in other threatened species, MLCD’s captive population has a large number of founder individuals. The genetic diversity of two captive populations of L. chrysomelas was evaluated by using 16 microsatellite loci (seven homologous and nine heterologous loci). The populations are held at Centro de Primatologia do Rio de Janeiro (CPRJ) and at Fundação Parque Zoológico de São Paulo (FPZSP) and we aimed to verify if genetic diversity has been maintained ex situ in comparison to in situ’s. Besides, we investigated possible correlations between fitness and individual heterozygosity. The fitness measure was the individual contribution for population growth (Pt) in a given time interval. We detected genetic differentiation between the two evaluated institutions due to lack of gene flow for some past generations. Our findings suggest that genetic diversity of these captive populations is similar to one measured in wild population of REBIO-Una&Ararauna, which is found in a single protected forest area that is large enough to retain an average or high density of MLCD and 98% of its genetic diversity. The individual heterozygosity effect on Pt fitness measure was verified just in CPRJ population. This correlation analysis indicates that the individuals from CPRJ with higher heterozygosity are leaving more offspring, which does not happen in FPZSP. The genetic diversity and correlation between fitness and individual heterozygosity results suggest that the management carried out in institutions is divergent.